A sociabilidade moderna e sua crise : um diagnóstico a partir da sociedade civil-burguesa e o tribunal na filosofia do direito de Hegel - Endler, Diego Süss (2012)
The objective of this work presents a concern that, even though it s absent from an effective proposal of short range solution, it s already a routine in the world. Along with the development of the modern society came also other factors that denoted a special attention in order not to make it a place of only negative elements in light of a universality that should watch for everyone. Hegel s civilian-burgeon society s theory shows itself able to identify why the modern human relations were antagonistic and made it unable to think in a union of interests that led to the freedom path in the state synthesis intended by the German philosopher. The human being while a social being aims, in first place, to satisfy his own desires without thinking of the risks that may possibly thwart the desires of others. If in society itself there weren t ways of limiting the lust from new aspirations of individuals belonging to it, a possible unit around common universal objectives would be unable. One way of limiting that Hegel understood as efficient in achieving this goal would be the very court activity that, in respect to the law that regulates all, would reestablish the lost universal standard due to any violation directed to it. This peculiarity inherent to the characteristics of Hegel s civil society, in Philosophy of Law, allows the generation of economical conflicts and miseries typical of a process of concentration of wealth, increasing disparities, as well as the occurrence of criminal activities. In this respect, the court would return to the law its universal content which, for Hegel, is the very right. The theory of civil society present in the Philosophy of Law offers an opportunity to diagnose, finally, the installation of a crisis in modern sociability and that got extended to the present. The court while a member of this painful mediation in search of the State has proven to be crucial to the overcome of this moment, but, nevertheless it is clear that its activity is still deficient in achieving this aim.